Tinjauan Yuridis Terhadap Perkawinan di Bawah Umur dalam Undang-Undang no 1 tahun 1974 dan Kaitannya dengan Hukum Islam - Umar Faruq (LP3M INSTITUT KH YAZID KARIMULLAH, 2022)
Article 1 of Law Number 1 of 1974 states that marriage is an inner and outer bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on God Almighty. Based on the provisions of Article 2 paragraph (1) which states that a marriage is valid if it is carried out according to the law of each religion and belief. And the provisions of Article 7 paragraph (1) Marriage is only permitted if the man reaches the age of 19 (nineteen) years and the woman has reached the age of 16 (sixteen) years. As for the problem in this thesis, what is the view of Law Number 1 of 1974 and Islamic law on underage marriages and the legal consequences if a marriage is still carried out according to the provisions of Law Number 1 of 1974 and the provisions of Islamic law. And what efforts must be made so that a marriage that is still underage becomes legal according to law. The research in this thesis was carried out using the Library Research method or library research by studying the legislation on a number of books, writings and scientific works related to the material discussed in this thesis. According to the provisions of Law Number 1 of 1974 that a marriage is considered valid if carried out according to their religion and belief and reach the age limit that has been determined in the Marriage Law. On the other hand, according to Islamic law, a marriage that has fulfilled the pillars and conditions of marriage is considered a valid marriage even though it does not reach the age limit specified in the law so that the legal consequences are the same as marriages in general. Therefore, the marriage is not valid according to positive law, then the marriage has no legal consequences, but there is an impact of underage marriage on the status of children and wives. That is in terms of inheritance and child recognition